STATUS MUTU AIR SUNGAI AYUNG BERDASARKAN DATA PEMANTAUAN KUALITAS AIR TAHUN 2014-2018 - I Made Sara Wijana; Ni Made Ernawati; Abd Rahman As-syakur (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2020)
It is very important to know the status of river water quality, in order to determine the direction of resource management which is decreasing in quality according to its allocation. Analysis of the status of the water quality of the Ayung River in Bali Province using secondary data in the form of data on illness results from 2014 to 2018. The number of parameters applied to the fire is 16 parameters with class II water quality standards referring to attachment XII of Bali Governor Regulation No. 16 of 2016 concerning Environmental Quality Standards and Environmental Damage Standard Criteria. The analysis used the Storetic Method (Decree of the Minister of Environment Number 115 of 2003). The results of the analysis show that the status of Ayung River water is at very good, good and moderate levels. The status of the Ayung River's air quality tends to decline from year to year and from upstream to downstream. Status determining parameters are: BOD5, phosphate, phenol, detergent and sulfide. Key words: water quality status; ayung river; storet.